Tenth National Convention of Marine Engineers and All India Seminar on Emerging Trends and Technologies in the Maritime Industry, 6th & 7th June 1996, Mumbai : souvenir & seminar document (Marine Engineering Division of the Institution of Engineers (India), Maharashtra State Centre, 1996)
Souvenir brought out on the platinum jubilee year of the Marine Engineering Division of the Institution of Engineers (India), Maharashtra State Centre.